The Influence of Principal’s Visionary Leadership on the Professional Competence of Teachers at A-Accredited Private Senior High Schools in Pamijahan District, Bogor - Siti Nurfaizah; Muzhir Ihsan; Ima Rahmawati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the influence of the principal's visionary leadership on the professional competence of teachers in A-accredited private senior high schools across Pamijahan District, Bogor. Methodology: This research employed a quantitative approach with a survey method. The collected numerical data were analyzed using simple linear regression analysis. The data collection technique involved a Likert-scale questionnaire with five response alternatives, consisting of both positive and negative statements. Findings: Based on the results of the regression test, a significance value of 0.000 < α (0.01) was obtained. Consequently, it can be concluded that there is a significant influence of the principal's visionary leadership on teacher professional competence.